The tricksters - Mahy, Margaret (London : HarperCollins, 2001)
While gathered together for the Christmas holiday, a large New Zealand family and their various guests and hangers-on find their lives suddenly invaded by three fascinating but rather sinister brothers and by New Year nothing is the same again.
Keywords: Christmas -- Fiction; Family problems -- Fiction; Interpersonal relations -- Fiction; Supernatural -- Fiction; New Zealand -- Fiction